(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The present paper expresses the idea of the possibility of using a non-destructive method of research by means of Barkhausen Noise Analysis (BNA – Barkhausen Noise Analysis), replacing the conventional destructive methods for the examination of nitrided layers, making evaluations and comparisons with them. The paper refers to a specially created methodology, the implementation of which consistently follows the presentation of the paper. Comparing the non-destructive testing methodology with tribological, mechanical and metallographic research can outline which of the analyses can be substituted and what accuracy can be relied upon for the substitution. Heat-resistant steel ВН21 was used as the object of research. The research is of practical value because the process has been established for this steel. The experience gained in this regard will help to expand and validate non-destructive testing methods.